3 research projects scored high marks at Archimedes 2011 - Mohamad Ilzam, Jamat
For the first time, Universiti Malaysia Pahang (UMP) submitted entries to the biggest exhibition and research competition in Russia – the 14th Moscow International Salon of Invention & Innovation Technologies (Archimedes) which was held at Sokolniki Eco Center, Moscow from April 5-9, 2011.